Legal Analysis of the Crime of Money Laundering Through Cryptocurrencies - Sigit Eka Putra; Rahmat Dwi Putranto (Fakultas Hukum Dehasen, 2022)
In the era of digital technology, various information, communication and even transaction activities take advantage of all forms of existing technological developments, one of the developments in digital technology that is currently often used in conducting economic transactions both in the form of trade and investment is the emergence of crypto currencies or commonly used in the market. call it Cryptocurrency. With the development of digital technology, it has a positive impact on a country, various components of society participate to take part in utilizing the development of digital technology in conducting economic transactions, especially investment activities. However, the existence of Cryptocurrencies also has a negative impact, with the difficulty of openness or transparency of information from cyprocurrencies, making it easy for criminals to take advantage of cryptocurrencies as a means of committing crimes, one of which is by using cryptocurrencies as a means of money laundering. regulation of money laundering crimes through cryptocurrency media, This study uses a normative method by conducting research through library research in answering the author's problem formulation and get the results that, using cryptocurrency becomes a new mode and makes it easier for perpetrators of money laundering crimes to commit these crimes, with the existence of Cryptocurrencies that provide convenience such as the closure of my identity, no checking accounts and third parties As a supervisor, it has an impact in facilitating a money laundering crime to occur.